Pemimpin Non Muslim dalam Analisa - Ropiah, Siti (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2023)
Abstract The issue of non-Muslim leaders often arises in society, sparking significant debate. Historically, this matter has been longstanding, consistently prompting discussions among scholars across eras. There exist two main perspectives: first, the view that having a non-Muslim leader is religiously prohibited, while others argue that it is permissible in Islam. The reference point for these opinions is the Quranic verse Al-Ma'idah 5:51. Controversy arises due to differing interpretations of the term 'awliya' and variations in understanding the context and reasons behind the revelation of the verse. Some interpret it strictly based on the text, while others consider the contextual relevance. Additionally, discrepancies arise from linking one verse's interpretation to others related to non-Muslim leadership. Keywords: Controversy, Non-Muslim Leaders, Awliya